Driving The Energy Transition: Comparative Investment Analysis of Owned and Leased Electric Motor Systems as Replacements for Diesel Pump Drivers in Oil Transportation Infrastructure - Teguh Wicaksono (Jurnal Locus Penelitian dan Pengabdian, 2026)
The oil transportation sector faces growing challenges from diesel fuel price volatility, increasing operational expenditures, and reliability concerns in diesel-driven pumping systems. PT Pertamina Gas, particularly in the Operation Central Sumatera Area, continues to rely on diesel pump drivers for crude oil transportation, resulting in cost uncertainty, intensive maintenance requirements, and exposure to mechanical downtime. This study aimed to compare the economic feasibility and long-term cost implications of ownership and leasing models for electric motor implementation as a replacement for diesel pump drivers. A mixed-methods approach was applied, combining quantitative financial analysis, lifecycle cost analysis, sensitivity analysis, breakeven analysis, and qualitative strategic assessment. The financial evaluation employed NPV, IRR, Payback Period, Profitability Index, and Life Cycle Cost over a 15-year project horizon with a WACC of 11.16%. The results indicated that the ownership model provided the strongest long-term value, with an NPV of Rp 23,494.2 million, an IRR of 47.95%, a Payback Period of 2.08 years, and a Profitability Index of 3.42. Ownership also demonstrated lower lifecycle costs, with a present value of Rp 13,285 million compared to Rp 40,744.7 million for the leasing model. Long-term leasing was not recommended due to negative NPV and escalating lease payments, whereas short-term leasing was justified only as a tactical bridging option when incremental throughput exceeded the breakeven threshold. This study concluded that ownership should be adopted as the primary long-term strategy to enhance cost efficiency, asset control, operational reliability, and to support the Pertagas energy transition agenda.